Pregnancy experience in the setting of cystic fibrosis: A systematic review and thematic synthesis. (12th July 2022) - Milo, Francesco; Tabarini, Paola
Abstract: Aims: To synthesize qualitative studies of subjective experience of pregnancy in people with cystic fibrosis. Design: Thematic synthesis of qualitative studies. Data sources: We searched PUBMED, CINAHL, EMBASE. PsicINFO and Social Sciences Citation Index for qualitative studies published in English, which reported on pregnancy in people with cystic fibrosis. Searches were carried out in March 2021, updated in June 2022. Review methods: Studies that met the inclusion criteria were appraised for quality using the Critical Appraisal Skills Programme (CASP) for qualitative research. Data were extracted from the studies, analyse and synthesise using thematic synthesis approach. Results: Thirteen studies were included in the review and 'Walking on a wire' framework was conceptualized. We found three analytical themes: (1) desire for information related to pregnancy in cystic fibrosis, (2) factors at play in decision‐making related to pregnancy for people with cystic fibrosis and (3) pregnancy experience and eight descriptive themes: (1) information topics, (2) CF healthcare team/PwCF as a provider of reproductive health information, (3) information timing, (4) barriers to information delivery, (5) barriers to decision‐making and stresses relating to the process of trying to conceive, (6) environmental factors, (7) coping with challenges, and (8) moving towards parenthood. Conclusion: For people with cystic fibrosis, pregnancy is a complex pathway: the amount of knowledge about cystic fibrosis and sexual and reproductive health, barriers to pregnancy and environmental factors provides the background to decision‐making. Moreover, coping with pregnancy is a challenging experience, where they have to mediate between the physical and emotional implications of planning a pregnancy and the limitations imposed by the chronic health conditions. Impact: Understanding the psychological experiences of people with cystic fibrosis (PwCF) will improve future research and practice. Education about sexual and reproductive health and psychosocial care programmes are necessary to help PwCF deal with the challenges related to pregnancy. Hospitals should enhance the development of specific programmes to promote the well‐being of individuals with CF who are planning a pregnancy.